An improved estimate on the degree of approximation to functions of bounded variation by certain operators (1995)
Guo introduced a modification Mn (f, x) of the Meyer-König- Zeller operators Mn (f, x) and gave an estimate on the rate of convergence to f of the modified operators when f is a function of bounded variation. In the present paper we establish a sharp estimate on the operators Mn (J, x) using some results in probability theory.